Actions and Adaptations Implemented for Maternal, Newborn and Child Health Service Provision During the Early Phase of the COVID-19 Pandemic in Lagos, Nigeria: Qualitative Study of Health Facility Leaders - Mobolanle Balogun; Aduragbemi Banke-Thomas; Uchenna Gwacham-Anisiobi; Victoria Yesufu; Osinachi Ubani; Bosede B. Afolabi (Ubiquity Press, 2022)
Background: The early phase of the COVID-19 pandemic led to significant disruptions in provision of maternal, newborn, and child health (MNCH) services, especially in low- and middle-income countries (LMICs) with fragile health systems, such as Nigeria. Measures taken to 'flatten the curve' such as lockdowns, curfews, travel restrictions, and suspension of public services inadvertently led to significant disruptions in provision of essential health services. In these countries, health facility leaders are directly responsible for driving changes needed for service delivery. Objective: To explore perspectives of health facility leaders in Lagos, Nigeria, on solutions and adaptations implemented to support MNCH service provision during the early phase of the COVID-19 pandemic. Methods: Key informant interviews were remotely conducted with purposively sampled 33 health facility leaders across primary, secondary, and tertiary public health facilities in Lagos between July and November 2020. Following verbatim transcription of recordings, data familiarization, and coding, thematic analysis was used to synthesize data. Results: Health facility leaders scaled down or discontinued outpatient MNCH services and elective surgeries. However, deliveries, newborn, immunization, and emergency services continued. Service provision was reorganized with long and staggered patient appointments, collapsing of wards and modification of health worker duty rosters. Some secondary and tertiary facilities leveraged technology like WhatsApp, webinars, and telemedicine to support service provision. Continuous capacity-building for health workers through training, motivation, psychological support, and atypical sourcing of PPE was instituted to be able to safely maintain service delivery. Conclusion: Health facility leaders led the frontline of the COVID-19 response. While they took to implementing global and national guidelines within their facilities, they also pushed innovative facility-driven adaptations to address the indirect effects of COVID-19. Insights gathered provide lessons to foster resilient LMIC health systems for MNCH service provision in a post-COVID-19 world.